Understanding the Challenges of Accessing University Support Services: The Perspectives of Staff Members and International Students - Harryba, S.; Guilfoyle, Andrew; Knight, Shirlee-ann (Common Ground Publishing, 2012)
International education is a worldwide phenomenon. Many countries host international students as part of their strategic directions to compete and function effectively in an age of globalization and as a way to advance their knowledge-based economy. Research shows that although international students (IS) bring economic and reported social and cultural benefits, they can experience difficulties when transitioning to university. To help lessen these difficulties, universities and host countries have developed support services to promote successful transition. However research demonstrates that there is a gap between service provision and utilisation, and that although IS need these services, they rarely access them. In this paper we reflect on data from qualitative interviews with a range of international students and university staff in an Australian university (n=73). The data suggests challenges such as perceived language and cultural barriers, unawareness of services, and being uncomfortable as being some of the reasons IS do not access services. It was concluded that specialised services for IS might optimise utilisation.